ANALISIS SISTEM PENGENDALIAN INTERN PENGGAJIAN KARYAWAN PADA BANK BTN DI SURABAYA - LALA WINANDA, ASTIKHA Lala (Jurnal Akuntansi AKUNESA, 2012)
The research objective was to determine the payroll system on Bank Tabungan Negara Surabaya. The research method used in this study is descriptive. Bank Tabungan Negara Surabaya as an object in this study. Primary data obtained from interviews on Bank Tabungan Negara employee Surabaya Assessment is done through a qualitative approach, namely by analyzing the system payroll and internal control systems. This proves that’s Bank Tabungan Negara Surabaya has pengganjian system and internal control systems are quite good. So as to meet the company's employee satisfaction. The results of the evaluation of payroll systems and procedures are adequate payroll company that due to the separation of functions, the aspects of organizational structure, aspects of the authorization system, aspects of the recording procedures, aspects of healthy practices in the internal control structure. Keyword: the payroll procedures, internal control system.